PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL BERBASIS APLIKASI CAMTASIA TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI LOGIKA MATEMATIKA - Eva margaretha Saragih (Universitas Asahan, 2019)
AbstractThis study aims to determine whether there is an effect of the use of Camtasia-based audio visual media onstudents' mathematics learning outcomes in class XI Mathematical Logic Material of Muhammadiyah 5Vocational School in Asahan Regency 2016/2017 Academic Year. This type of research is quasiexperimental, which is the sample of the study there are 2 classes (class XI AP-1 and XI AP-2) taken incluster random.Then given a different treatment, the experimental class with the conventional Visual Assisted MediaLearning learning model and the control class with conventional methods. After the learning was completed,posttest was obtained with the results of the experimental class averages 78.7 and the control class 74.7. Theresults of t-test obtained thitung = 2.10> t table = 1.67 then Ha is accepted, thus it can be concluded thatthere is influence of the use of Camtasia-based Audio Visual Media on Student Mathematics LearningOutcomes in Class XI Mathematical Logic Material of Muhammadiyah 5 Kisaran District Asahan2016/2017 Academic Year.Keywords: Use of Camtasia Application-Based Audio Visual Media, learning outcomes, MathematicalLogics